Identifikasi Kesulitan Guru dalam Menyusun Instrumen Penilaian Anak Berkebutuhan Khusus - Hasanah, Mutia Nur; Nur'aini, Hepy Dwi; Aliyah, Himmatul; Putri Aji, Jiva Laelatl Fitri; Azuma, Muhammad Afrizal; Khoiriyah, Mustaufiyatul Nur; Salsabila, Rifdah Nur (Jurnal Penelitian Pendidikan Khusus, 2023)
The background of this research is that there are still many teachers who have difficulty in compiling appropriate assessment instruments for children with special needs. The goal to be achieved in this research is to identify and describe teacher difficulties in compiling assessment instruments for children with special needs so that solutions can be found that help teachers carry out their duties. This study uses a quantitative method with data collection techniques from previous research journals. The research results that have been obtained are then analyzed using descriptive analysis techniques. The results of this study indicate that there are still many teachers who experience difficulties in compiling assessment instruments due to the lack of standard curriculum references for students with special needs, in addition to the teacher's lack of ability to identify the types of needs of students with special needs. The solution that can be done by the teacher is to form a special team to design learning for children with special needs, besides that the teacher must also be able to map students based on the type of difficulties and their needs so that they can determine the appropriate assessment instrument